Peranan Partai Keadilan Sejahtera (PKS) dalam Meningkatkan Partisipasi Masyarakat pada Pemilihan Umum Tahun 2024 di Kota Padang - Rosma Mayar; M. Fachri Adnan (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research was conducted with the aim of explaining the role of the PKS party in increasing Political Participation in the 2024 General Election in Padang City This research uses a qualitative descriptive approach. Data collection was carried out through interviews and documentation studies. In determining the informant, the technique used is purposive sampling. The informants consisted of the Chairman of the Padang City PKS DPD, the Secretary of the Padang City PKS DPD, the deputy secretary of the Padang City PKS DPD, and the Padang City Community. The validity in this study uses the triangulation technique of data sources and methods. The data analysis technique in this study uses Manual Data Analysis Proedure (MDAP), which is qualitative data analysis that is carried out manually, namely daily notes, transcripts, coding, categorization, themes and memos. The results of the study show that the Prosperous Justice Party (PKS) in Padang City plays an important role in increasing public participation in the 2024 General Election. Through various political socialization strategies, such as political education, socialization of programs, campaigns, and candidates, PKS has succeeded in introducing political values, work programs, and the party's visions and missions to the public. Factors that affect the role of the PKS party in increasing public participation in the 2024 general election in Padang City include socialization media factors, party administrators, party members, and the type and form of programs